Anti-Cancer Drugs: Molecular Mechanisms of Action - Isoldi, Mauro C.; Visconti, Maria Aparecida; Castrucci, Ana Maria de Lauro (Mini Reviews in Medicinal Chemistry, 2005)
Genetic alterations are responsible for all cancers. These mutations produce, in turn, alterations in key proteins of certain signaling pathways. Amongst the best known and studied alterations related to malignant transformations are those which occur in Ras protein and p53. In most cases mutations in Ras and p53 lead to the appearance of practically most malignant transformations. Mutated Ras genes exist in approximately 20 to 30% of all human cancers. Ras proteins are switches that regulate diverse functions such as cell proliferation, differentiation and apoptosis. Normal p53 expression, also known as the “genome guardian”, is a key molecule for suppressing cell proliferation. The great importance of these proteins rests on their intimacy with the events leading to cell proliferation or death. The comprehension of the extent of transformation on Ras and p53, and of the diverse biochemical pathways of intracellular signaling, activated by them, is of extreme importance for the understanding of malignant transformation, as well as its control, through the creation, for example, of new drugs which contribute to the elimination of these cells. To clarify the consequences originated by transformed Ras, p53 and their biochemical interlinks in the different intracellular pathways, besides the possible intervening points and pharmacological controls presently used in combating cancer, are the aims of this review.
Keywords: cell signaling